RESISTANCE TO GENDER STEREOTYPES: AN ANALYSIS OF THE CHARACTER FARCHAH IN THE FILM BY DARIN J. SALLAM - Ramandhani, Intan; Nugraha, Reza Sukma (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Abstract This study investigates the portrayal of gender stereotypes and women's resistance in the film Farchah (2021) by Darin J. Sallam. The research focuses on analyzing the textual representation of female stereotypes and the character Farchah's resistance to them, using Naomi Wolf's feminist theory as the analytical framework. The study employs a qualitative descriptive method combined with library research to analyze primary data in the form of dialogues and scenes from the film, as well as secondary data from relevant literature. Data were collected through documentation techniques and analyzed systematically to identify patterns and meanings in the text. The findings reveal five dominant stereotypes imposed on women in the film: (1) women must marry early; (2) women do not need higher education; (3) women should stay close to home; (4) women are expected to cook; and (5) women are inherently weak. Additionally, the study identifies corresponding acts of resistance by Farchah, including: (1) rejecting an arranged marriage; (2) pursuing education; (3) aspiring to live in the city; (4) refusing to conform to traditional cooking roles; and (5) displaying physical and psychological courage by escaping confinement and using firearms. This research contributes to feminist film studies by demonstrating how Farchah challenges traditional gender roles and highlights women's agency in confronting societal expectations.